2004
DOI: 10.1021/ac049092r
|View full text |Cite
|
Sign up to set email alerts
|

pH/Organic Solvent Double-Gradient Reversed-Phase HPLC

Abstract: A new reversed-phase high-performance liquid chromatographic (RP HPLC) procedure has been theoretically and experimentally established. The approach consists of the simultaneous development of a gradient of pH and of the organic modifier in the mobile phase. The proposed theoretical model of the pH/organic solvent double-gradient RP HPLC allows determination of both pK(a) and the lipophilicity parameter of the ionized and the nonionized form of the analyte and prediction of the retention times at specific sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…We firstly employed high pH (pH 10) RP-LC (13,24) to decrease the complexity of the tryptic digest of the HeLa total cell lysate. We collected 24 fractions in the first dimension RP-LC of a 72-min gradient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We firstly employed high pH (pH 10) RP-LC (13,24) to decrease the complexity of the tryptic digest of the HeLa total cell lysate. We collected 24 fractions in the first dimension RP-LC of a 72-min gradient.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed the outstanding capability of 2-D RP-RP system in peptide separation (13,24,37). RP-RP approaches using two different pH values were further demonstrated to have good potential in fractionating complex protein mixtures (14,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Certain types of multi-modal separation are truly multidimensional. One example was running a simultaneous pH and organic gradient across a RP-HPLC column (Wiczling et al, 2005) so that all analytes were subjected to both mechanisms. This is one of the few techniques where the analytes are simultaneously subjected to both separations in a two-dimensional separation.…”
Section: Planarmentioning
confidence: 99%
“…Reversed-phase high-performance liquid chromatography (RP HPLC) allows determination of pK a and lipophilicity related parameters (chromatographic measure of hydrophobicity, log k w ) [5][6][7][8][9][10][11][12][13]. Lipophilicity and dissociation constant determination by HPLC have already been described in literature.…”
Section: Introductionmentioning
confidence: 99%